Identifying key industries of Vietnam based on science, technology and innovation: international experiences and implications for Vietnam - Nguyen, Quynh Anh; Nguyen, Thi Bich Phuong; Nguyen, Van Hieu (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
The identification of key industries plays an important role in countries to properly support them for economic development, and serving as a driving force to lead other industries. This paper explores science, technology and innovation criteria and how to use these criteria to identify key industries in line with the knowledge-based economic development approach in 21st century from international experience. The implication for science, technology and innovation criteria and corresponding methodology for identifying of key industries in Vietnam are recommended